Altered mental status and fever. (24th June 2013) - Ajayi, Tokunbo; Bhatia, Ashmeet; Lambl, Barbara; Altamimi, Sarah
Abstract : West Nile virus (WNV) is still the most common cause of neuroinvasive arboviral disease in the USA with a case death of 10–30%. We are reporting a case of a 61-year-old woman with a history of Crohn's disease, fibromyalgia treated with chronic steroid therapy that presented with a day history of fever, confusion and lethargy. She had a lumbar puncture which was notable for lymphocytosis and was positive for WNV. She initially was treated with broad-spectrum antibiotics, which were subsequently discontinued when the diagnosis of WNV neuroinvasive disease (WNND) was made. A high index of suspicion is needed to diagnose WNND, and this should be suspected in elderly immunocompromised patient presenting with altered mental status and lumbar puncture suggestive of aseptic meningitis. Recent study has showed that there is genetic variation in the interferon response pathway which is associated with both risk for symptomatic WNV infection and disease progression.